The DICA has arrived! The Science Center of Universidade Federal de Uberlândia: proposal, professors perceptions and perspectives - Jacobucci, Daniela Franco Carvalho; Takahashi, Eduardo Koji; Jacobucci, Giuliano Buzá; Carmo-Oliveira, Renata; Martins, Silvia (Caderno Brasileiro de Ensino de Física, 2008)
This paper presents the proposal of the Science Center of the Universidade Federal de Uberlândia (UFU), the DICA Diversão com Ciência e Arte (Entertainment with Science and Art), and a qualitative research on the perceptions of the university professors of the Physics and Biology Institutes of the UFU in relation to the scientific divulgation, the space that is being established as a Science Center and their interest in participating of the DICA actions. The professor s statement evidences that the most of them are interested in acting in the Center developing scientific divulgation activities related to their own scientific researches. However, only one interviewed researcher wanted to develop researches on Science Education linked to the Science Center.